E-Marketing Determinants of Bank Syariah Indonesia Mobile Banking Customer Loyalty (Study D.I. Yogyakarta) - Hamidah, Hamidah; Indana, Rifaatul (Journal of Islamic Economic Scholar, 2025)
This study aims to examine the influence of e-trust, e-service quality, e-satisfaction, and electronic word of mouth (e-WOM) on customer loyalty among users of Bank Syariah Indonesia’s mobile banking services in the Special Region of Yogyakarta. Using a quantitative approach and multiple linear regression analysis on 110 respondents, the results show that e-satisfaction and e-WOM have a positive and significant effect on customer loyalty, whereas e-trust and e-service quality do not have a significant effect. Collectively, the four variables explain 54.9% of the variation in customer loyalty. These findings emphasize the critical role of satisfaction and digital recommendations in sustaining user loyalty in mobile Islamic banking services.